2015
DOI: 10.1175/jhm-d-15-0009.1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Remote Sensing Data on Evapotranspiration and Leaf Area Index with Hydrological Modeling: Impacts on Model Performance and Future Predictions

Abstract: Using the Connecticut River basin as an example, this study assesses the extent to which remote sensing data can help improve hydrological modeling and how it may influence projected future hydrological trends. The dynamic leaf area index (LAI) derived from satellite remote sensing was incorporated into the Variable Infiltration Capacity model (VIC) to enable an interannually varying seasonal cycle of vegetation (VICVEG); the evapotranspiration (ET) data based on remote sensing were combined with ET from a def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…Historical observations and future predictions from global and regional climate models indicate that both the magnitude and the frequency of extreme precipitation increase obviously 15 , while the annual mean precipitation is detected to increase less than extreme precipitation or even decrease 6 , which may cause drought and flood risks 7,8 . Hence, prediction of precipitation, especially for precipitation extremes, is of significant importance to enhance the adaptivity of human beings to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Historical observations and future predictions from global and regional climate models indicate that both the magnitude and the frequency of extreme precipitation increase obviously 15 , while the annual mean precipitation is detected to increase less than extreme precipitation or even decrease 6 , which may cause drought and flood risks 7,8 . Hence, prediction of precipitation, especially for precipitation extremes, is of significant importance to enhance the adaptivity of human beings to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, drought is exacerbated in some regions because of enhanced evapotranspiration (Zhai et al, 2007). The net effect is that intense precipitation and drought will increase in frequency and severity with global warming (Parr et al, 2015). Thus, it is of great importance to project changes in precipitation extremes for a warming future world.…”
mentioning
confidence: 99%
“…More work on the uncertainty relationship among precipitation, ET and surface runoff are needed in the future. Historic ET data can be used to correct the ET components estimations, which affect surface runoff generation in VIC [18]. The ET components estimations in GSWAT model have little effect on surface runoff generation.…”
Section: Synthetic Experimentsmentioning
confidence: 99%
“…Remotely sensed evapotranspiration can be used for hydrological model parameter calibration or estimation, which can affect the surface runoff generation [10,12,13,16,17]. Parr et al [18] found that hydrological predictions may be subject to the bias in past ET modeling, leading to substantial uncertainties in the modeled hydrological trend. They replaced the simulated ET components (canopy evaporation, transpiration, bare ground evaporation, canopy sublimation, and surface sublimation) of the VIC model with the bias-corrected ET calculated from a simple bias-correction algorithm and historic remotely sensed ET.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation